The Role of PAI Teachers in Shaping Islamic Character Child with Autism at Mysarah Kindergarten Padang Serai, Malaysia - Anggraini, Sri Veronica; Zuliana, Zuliana (Al-Ulum: Jurnal Pendidikan Islam, 2025)
This research investigates how Islamic Religious Education (PAI) learning shapes Islamic character in children with autism. This research was conducted using a descriptive qualitative case study methodology. Data were obtained through interviews, observations, and documentation, and thematic analysis was used to test the results. This research aims to provide information for educators and policymakers on how to create more effective and responsive educational programs for autistic children by teaching Islamic Religious Education and also shaping the character of autistic children at Tadika Mysarah. The results of this study highlight the important role of Islamic Religious Education (PAI) teachers in character development, strengthening Islamic principles, and offering spiritual guidance through an open and flexible approach. Islamic Education teachers are very important in instilling Islamic values in children with autism, especially by collaborating with parents and related experts to create child-friendly teaching methods. Research also shows that tailored learning can enhance a child's understanding of Islamic teachings, help them build self-confidence, and develop social skills. The teaching methods used include educational games, Islamic stories, and simple worship practices, which are designed to meet the special needs of autistic children.